The impacts of landscape structure changes on urban surface temperature and heat islands formation of a growing city in southern Sri Lanka - Chanuwan Wijesinghe, Dilnu; Withanage, Neel Chaminda; Mishra, Prabuddh Kumar; Frenando, Wasana Surandi; Abdelrahman, Kamal; Fnais, Mohammed S. (Frontiers in Environmental Science, 2024)
Undoubtedly, urbanization has improved human living conditions. However, it has also altered the natural landscape, leading to negative consequences such as increased Land Surface Temperature (LST) and Urban Heat Island (UHI) due to the expansion of Impervious Surface (IS). Much research has been conducted in other countries on the effects of changing urban landscape structures on LST and UHI formation. However, in Sri Lanka, only a few studies have been available on this topic, primarily concentrating on major cities like Colombo. Impervious Surface is absorbing high amounts of solar energy as well, which accelerates the magnitude of UHI in urbanized areas. Remote Sensing indices such as the Normalized Difference Vegetation Index (NDVI), Normalized Difference Buildup Index (NDBI), UHI, and Environmental Criticality Index (ECI) can effectively be used to quantify the intensity of the UHI phenomenon. This study aimed to investigate the effect of spatiotemporal variations in IS and Green Surface (GS) on UHI, LST, and the environmental criticality in Galle Municipal Council (MC), Sri Lanka employing multi-temporal Landsat-5 and 8 data from four different periods: 1996, 2005, 2014, and 2022. Different geospatial techniques including supervised image classification, Urban-Rural Gradient Zone (URGZ) analysis, grid-based analysis, UHI profiles, and regression analysis were used in the study. The findings revealed that Impervious Surface increased by 42.3% (7.34 km2) while Green Surface had a decline of 22.5% (3.91 km2) during the concerned period. This landscape transition led to a 2.74 C increase in mean surface temperature in the study area, along with a 9.5 C increase in the UHI index during 26 years. The results further revealed that Impervious Surface rapidly developed within 4 km (URGZ1-19) from city center, while Green Surface decreased. Newly built-up areas within the 1.5 km gradient (URGZ1-URGZ8) were more affected by increased LST. A positive correlation was identified between NDBI and LST, especially in the year 2022, with an R2 of 0.457, while NDVI and LST reported a negative R2 of 0.257. The grid-based analysis demonstrated an increasingly positive relationship between mean LST and the fraction of Impervious Surface, highlighting the role of built-up areas in raising LST and UHI in the MC. As a result, very high environmental critical areas have been concentrated in and around high-density Impervious Surface. Thus, it can be predicted that the UHI effect and Environmental Criticality (EC) may increase further in the future. In this context, planning agencies should prioritize green urban planning strategies, such as implementing green belts and urban agriculture in the study area, particularly in and around areas with high LST and high environmental criticality. This approach may help protect the natural environment and sustainably ensure the health of the urban community.